Characterisation of various fly ashes from Australia and Mongolia and their utilisation for preparation of Geopolymers with advanced applications - Jadambaa, T.; Minjigmaa, A.; Rickard, William; Van Riessen, Arie (Research Publishing Services, 2012)
Fly ashes from different power stations of the Australia (Collie, Eraring, Tarong) and Mongolia (Darkhan, 3rd and 4th thermal power stations, Ulaanbaatar city) have been characterised by different techniques. It was determined that the Australian fly ashes are class F while most of Mongolian fly ash is class C. Due to their chemical and mineralogical differences the fly ashes behave differently when alkali activated to make geopolymers. The influences of various parameters on the preparation of geopolymers have been investigated and established for routine manufacture. The applicability of using fly ash for building structural elements, acid and alkaline resistant products and thermal resistance materials will be presented.